Organoleptic qualities and proximate composition of fish grown in good aquaculture practice-based carp fattening pond - Md. Anwar Hossain; Md. Akhtar Hossain; Md. Ayenuddin Haque; Mst. Nurjahan Begum (Journal of Fisheries, 2023)
Organoleptic qualities and proximate composition of fish grown in carp fattening pond were studied under three treatments of feed and fertiliser management. Treatment T1 was designed with the use of organic fertiliser and stocking of silver carp, T2 with both organic and inorganic fertilisers and silver carp and T3 with both organic and inorganic fertilisers but excluding silver carp. One day in a week feeding restriction was followed in all the treatments.  Fishes were stocked with a stocking density of 2470 fishes ha–1. Three fishes (Gibelion catla, Labeo rohita and Cirrhinus cirrhosus) were selected for organoleptic and proximate assessment. Cyanobacteria along with total phytoplankton cell density was significantly higher at treatment T2 followed by T3 and T1. However, in terms of productivity (Chl-a) treatment T2 was 27.1 and 13.3% higher compared to T1 and T3 respectively. Parameters assessed for proximate composition analysis did not vary across treatments and organoleptic test revealed comparatively higher acceptability of fishes collected from treatment T1 followed by T2 and T3 for all the fishes. Overall acceptability was higher for L. rohita from treatment T1. This study concluded that, inorganic fertilisation along with silver carp can improve the organoleptic properties of carps in pond.